Արցախի Հանրային հեռուստատեսության զարգացման հեռանկարները - Բալայան, Սամվել
Сегодня в ежедневном потоке технологических революций телекомпания встала на путь коренных преобразований. Действительно, традиционное телевидение изо дня в день уступает свои позиции. Зритель диктует изменения, удовлетворения современных требований. В противном случае, необратим проигрыш интернету и полное исчезновение. В армянской медиасфере Арцахскому общественному телевидению предстоит сделать многое, чтоб уверенно встать в один ряд с другими телекомпаниями. Вызовы становятся серьезнее, когда речь заходит о технологическом прогрессе и, соответственно, о развитии новых медиа. In the everyday flood of technological revolutions today's television stations have taken the way full of revolutions. The reality is that traditional TV is losing its position every day. The viewer demands to change and meet the modern requirements. Otherwise, the TV will irrevocably lose in the competition with the Internet and disappear. In order to stand firmly alongside other TV companies of the Armenian media field, the Public Television of Artsakh has still a lot to do. Challenges are becoming more serious when it comes to promoting technology and, consequently, the development of new media.
Keywords: Լրագրություն